2020
DOI: 10.1016/j.toxrep.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

N,N’ bis-(2-mercaptoethyl) isophthalamide induces developmental delay in Caenorhabditis elegans by promoting DAF-16 nuclear localization

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…The results showed that 12.5 and 25 μM ACR exposure decreased the cytosolic localization of DAF-16 (decreased to 22.2% and 7.8%), suggesting that the low concentration of ACR activated the antioxidant resistance caused by DAF-16/FOXO ( Figure 7 ). It was consistent with the findings that exposure to pharmaceuticals which induce oxidative stress, such as H 2 O 2 , N , N ′ bis-(2-mercaptoethyl) isophthalamide, juglone, and so on, could lead to the DAF-16 nuclear translocation [ 38 , 39 , 40 ]. It is worth noting that, with high exposure to ACR, the percentages of DAF-16 nuclear localization were decreased significantly (50 μM, 43.8%; 100 μM, 16.0%) ( p < 0.01) as compared to those treated with 25 μM of ACR, and this is similar to what was found in chronic exposure of zearalenone [ 41 ].…”
Section: Resultssupporting
confidence: 89%
“…The results showed that 12.5 and 25 μM ACR exposure decreased the cytosolic localization of DAF-16 (decreased to 22.2% and 7.8%), suggesting that the low concentration of ACR activated the antioxidant resistance caused by DAF-16/FOXO ( Figure 7 ). It was consistent with the findings that exposure to pharmaceuticals which induce oxidative stress, such as H 2 O 2 , N , N ′ bis-(2-mercaptoethyl) isophthalamide, juglone, and so on, could lead to the DAF-16 nuclear translocation [ 38 , 39 , 40 ]. It is worth noting that, with high exposure to ACR, the percentages of DAF-16 nuclear localization were decreased significantly (50 μM, 43.8%; 100 μM, 16.0%) ( p < 0.01) as compared to those treated with 25 μM of ACR, and this is similar to what was found in chronic exposure of zearalenone [ 41 ].…”
Section: Resultssupporting
confidence: 89%